EVALUASI PENERAPAN PSAK NO. 45 DAN PENGENDALIAN INTERNAL GEREJA DI WILAYAH SURABAYA, SIDOARJO DAN GRESIK - Agung Sriwardhani (Jurnal Bisnis Terapan, 2021)
Abstract This study aimed to evaluate the application of PSAK 45 accounting and internal control in 32 churches in the Surabaya, Sidaorjo and Gresik areas. The method used in this research was descriptive research by comparing the results of the study with existing theories. These are the results of this study. First, There is no strict separation of functional responsibilities, where the 26 churches have not separated the functions, while another 12 churches have clearly separated the responsibilities. Second, only 5 churches have implemented complete accounting records starting from the use of journals, general ledgers and financial reports produced by the church in accordance with PSAK 45.Third, the implementation of healthy practices in carrying out their duties and functions has not been implemented properly due to the small number of church administrator. Fourth, Employees do not have the appropriate quality and responsibility yet, because it is difficult to find people who are committed to doing services in the church. Keywords: church accounting, psak 45, church finances, internal control.